Marriage in The Late of 19th Century Reflected in The Age of Innocence - Hasnani Hasnani (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The Age of Innocence presents marriage woman in sociocultural background of upper-middle class woman in the late of 19th century. This research aimed to describe marriage in the alte of 19th century reflected in The Age of Innocence. The researcher used qualitative method. The data were analyzed by using the Sociological theory in order to describe marriage in the novel. The sociological theory is uesd to analysed the sociological background of marriage woman at that time. The results of the research shows marriage in the late of 19th century that describe in two parts; woman as fiancee and woman as a wife. The Age of Innocence represent the marriage women are still patriacy and in the domestic sphere